Analysis Of The Effectiveness Of Accounting Information System On Cash Receipts At Bank Syariah Indonesia KCP Surabaya Ampel Mas Mansyur - Devina Setya Vanessa; Sri Trisnaningsih (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Bank Syariah Indonesia (BSI) is the result of a merger of three existing Islamic banks in Indonesia, namely (i) Bank Mandiri Syariah; (ii) Bank BNI Syariah; and (iii) Bank BRI Syariah. With this merger, BSI can become an Islamic bank with better services, has a wider range, and has a better capital capacity. BSI's cash receipt accounting information system is very important in managing the company's finances which allows the company to manage funds more effectively and efficiently. The cash receipt accounting information system at BSI bank will enable the company to improve the financial services provided and improve better financial performance. With various advantages, Bank BSI is expected to be able to offer services and have better capital capacity to compete at the global level. This research uses a qualitative method with a case study. The data in this study were obtained through in-depth interviews with parties related to the cash receipt information system at Bank Syariah Indonesia KCP Surabaya Ampel Mas Mansyur and data literature through the BSI web. This study aims to determine the effectiveness of the accounting information system for cash receipts at Bank Syariah Indonesia KCP Surabaya Ampel Mas Mansyur and the results of this study are expected to be information to the public regarding the development of Bank Syariah Indonesia.